ARABISTIKA: JENDELA KECIL KAJIAN ISLAM DI RUSIA (Menelisik Sejarah Awal Pertumbuhan Kajian Islam di Rusia Abad IX-XVIII M) - Z, Wan Jamaluddin (Universitas Islam Negeri Raden Intan Lampung, 2011)
Study on the Islamic studies tradition (orientalism) in Russia is quite rare, whereas compared to the Europeans or the West in general, the Russians actually have far reached into contact with Islam through a variety of traditions and cultures that developed the Arab-Muslim and Arab-Jewish. This encounter in the next stage turned into the birth of a tradition encouraging the study of Russian orientalism known as arabistika. This article attempts to trace the history of the growth of Islamic studies in Russia by looking at the factors driving its development and the official policies of the country’s political elite, especially of Peters the Great. The author, in this context, tries to analyze the findings of I.Yu Krachkovsky on spiritual tour performed by Russian intelligentsia to the Arab world, and the sources of Muhammad Na>zim ad-Daira>wi revealing the information and documentation of ancient Russian that are immortalized by the some geographers, historians, prominent Muslim adventurers such as at-Tabari, al-Maqdisi, al-Idri>si>, al-Mas‘u>di>, Ibn Khurdadbih, Ibn Hauqal, Ibn Fadla>n, Ibnu Batu>ta and many others. This paper also reveal many of the central role of Peter the Great in the development of arabistika tradition in Russia.